2005
DOI: 10.1051/0004-6361:20042589
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration at a three-dimensional reconnection site in the solar corona

Abstract: Abstract. We study test particle trajectories in the vicinity of a three-dimensional (3D) magnetic null point during spine reconnection. Particles are injected into the steady-state non-uniform magnetic and electric fields derived by Priest & Titov (1996), and the equations of motion numerically integrated. We use input parameters typical of the solar corona, for which reconnection has been suggested as the fundamental mechanism responsible for particle acceleration in flare events. We show that substantial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 24 publications
3
96
0
Order By: Relevance
“…15 and further studied by Ref. 18. Particles which travel very close to the null point gain the most energy since they are directly accelerated by the electric field there.…”
Section: A Case I: Sheared Magnetic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…15 and further studied by Ref. 18. Particles which travel very close to the null point gain the most energy since they are directly accelerated by the electric field there.…”
Section: A Case I: Sheared Magnetic Profilementioning
confidence: 99%
“…18 Reference 14 performed numerical simulations of the non-relativistic particle motion in an X-type magnetic null configuration and found that particle trajectories in the non-adiabatic region close to the null are chaotic a) a.d.gascoyne@sheffield.ac.uk in nature and quantified this by calculating a positive value for the maximum Lyapunov exponent.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of magnetic reconnection in null-points in astrophysical and space plasmas were performed with MHD (Galsgaard & Nordlund 1997;Galsgaard & Pontin 2011) and kinetic (Baumann & Nordlund 2012) codes. The testparticle studies by Dalla & Browning (2005); Stanier et al (2012) found that null-points were able to accelerate particles to the energies, observed in solar flares.…”
Section: Introductionmentioning
confidence: 99%
“…When considered in isolation (depending on how the reconnection itself proceeds), various effects including drifting, mirroring, and acceleration have been studied in reference to both protons and electrons in a number of different experiments (e.g. Dalla and Browning, 2005, 2008Stanier, Browning, and Dalla, 2012). In our experiment, we see no evidence of mirroring and a minimal impact of drifts.…”
Section: Comparison With Topological Reconnection Modelsmentioning
confidence: 79%
“…Examples include several regimes of 3D null-point reconnection (e.g. Dalla and Browning, 2005, 2008Guo et al, 2010;Stanier, Browning, and Dalla, 2012), magnetic separator reconnection (e.g. Threlfall et al, 2015Threlfall et al, , 2016a or reconnection at fragmented current sheets (e.g.…”
Section: Introductionmentioning
confidence: 99%